Моделювання вдосконаленого теплообмінного блоку з мікроканалами для комбінованої фотоенергетичної установки - Зайцев, Р.В. (Електротехніка і електромеханіка, 2017)
У роботі розглядаються особливості підбору теоретичного підґрунтя та математичне моделювання теплових процесів у теплообмінному блоці для комбінованої фотоенергетичної установки. За результатами моделювання проведено вдосконалення та розробку високоефективного теплообмінного блоку з мікроканалами. Апробація запропонованого
блоку підтвердила його високу ефективність за рахунок реалізації турбулентного режиму протікання теплоносія.
Використання такого теплообмінника дозволить підвищити якість і рівномірність охолодження сонячних батарей
та зменшити витрати енергії на циркуляцію рідини. процессов в теплообменном блоке для комбинированной фотоэнергетической установки. По результатам моделирования проведено совершенствование и разработка высокоэффективного теплообменного блока с микроканалами. Апробация предложенного блока подтверждает его высокую эффективность за счет реализации турбулентного режима протекания теплоносителя. Использование такого теплообменника позволить повысить качество и равномерность охлаждения солнечных батарей и уменьшить затраты энергии на циркуляцию жидкости. Purpose. Mathematical modeling of the heat exchange unit main
parameters for photoenergy system based on general models
with forced circulation of heat transfer fluid. Methodology. To
determine the coefficient of heat transfer at a given coolant temperature and surfaces temperature necessary to determine the
temperature gradient in the wall of the heat exchanger. Temperature gradients can be determined by solving the equation of
energy, which depends on the distribution of the flow rate in the
flow. In general, a solution of convective heat transfer fluid to
flow along the plane comes to solution of the system of differential equations. Results. In the paper features of the selection of
theoretical basis and mathematical modeling of thermal processes in the heat exchange unit for combination photoenergy
system are presented. As a result of the simulation conducted we
improve and develop high-efficiency heat exchange unit with
microchannels. Testing of the proposed unit proved its high
efficiency through the implementation of turbulent flow of coolant with heat transfer coefficient at 18 kW/(m2
K). Analytical
testing of the heat exchanger allowed showing that heat exchanger unit provides a stable operating temperature at less
than 50 °C with the coolant flow rate is less than 0.3 m/s. Originality. Novelty of the proposed heat exchanger is in the optimal
design of microchannels to improve the heat transfer coefficient.
Practical value. The use of this heat exchanger will improve the
quality and uniformity of cooling solar panels and reduce energy costs for circulation of fluid